Risk management during COVID-19: safety procedures for otolaryngologists : Risk management for otolaryngologists - Spinato, Giacomo; Gaudioso, Piergiorgio; Boscolo Rizzo, Paolo; Fabbris, Cristoforo; Menegaldo, Anna; Mularoni, Francesca; Singh, Bhuvanesh; Maniaci, Antonino; Cocuzza, Salvatore; Frezza, Daniele (Acta Biomedica Atenei Parmensis, 2021)
The pandemic caused by SARS-CoV2 has stressed health care systems worldwide. The high volume of patients, combined with an increased need for intensive care and potential transmission, has forced reorganization of hospitals and care delivery models. In this article, are presented approaches to minimize risk to Otolaryngologists during their patients infected with COVID-19 care. We performed a narrative literature review among PubMed, Scopus and Web of Science electronic databases, searching for studies on SARS-CoV2 and Risk Management. Standard operating procedures have been adapted both for facilities and for health care workers, including the development of well-defined and segregated patient care areas for treating those affected by COVID-19. Personal protective equipment (PPEs) availability and adequate healthcare providers training on their use should be ensured. Preventive measures are especially important in Otolaryngology-Head and Neck Surgery, as the exposure to saliva suspensions, droplets and aerosols are increased in the upper aero-digestive tract routine examination. Morever, the frequent invasive procedures, such as laryngoscopy, intubation or tracheotomy placement and care, represent a high risk of contracting COVID-19.